Payment security and efficiency: Strengthening consumer trust in halal food purchases through Shopeefood user experience - Ryan Putra Ardiyansyah; Muhammad Sholahuddin (Universitas Nusa Cendana, 2026)
This study aims to examine the effects of digital transaction security and payment system efficiency on consumer trust in ShopeeFood, while investigating the mediating role of user experience in the context of halal food purchases. An explanatory quantitative research design was employed using data collected from 150 ShopeeFood users who had purchased halal food through the platform. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that both digital transaction security and payment system efficiency have positive and significant effects on consumer trust. Payment system efficiency also has a positive and significant effect on user experience. However, digital transaction security does not significantly influence user experience, and user experience neither has a significant effect on consumer trust nor mediates the relationships between digital transaction security, payment system efficiency, and consumer trust. These findings suggest that consumer trust in halal digital food delivery is driven primarily by functional aspects of secure transactions and reliable payment systems rather than by users' application experience. The study contributes to the literature on halal digital commerce by extending understanding of trust formation in online food delivery platforms and offers practical implications for platform providers seeking to strengthen consumer confidence through enhanced transaction security and payment reliability. Keywords: Consumer Trust; Digital Transaction Security; Efficient Payment System; Halal Food; User Experience